PEMBERDAYAAN KADER DETEKSI DINI GANGGUAN PERTUMBUHAN ANAK DENGAN METODE TIKAR STUNTING SEBAGAI UPAYA PENCEGAHAN STUNTING DI KELURAHAN TAPA, KECAMATAN SIPATANA, GORONTALO - Apriana, Rista; Syahrir, Akifa; Buheli, Kartin (Devote: Jurnal Pengabdian Masyarakat Global, 2023)
Gorontalo Province is one of the areas that has a fairly high prevalence of stunting. Several ways that can be done to reduce the risk of stunting is through early prevention which is carried out routine screening and follow-up on children's growth. This community service aims to increase cadres' knowledge about preventing and handling stunting as well as improving cadres' skills in carrying out early detection of stunting. The activities were done with a target of 20 health cadres in Tapa Village during July-September 2023 which consisted of 2 stages as follows: 1. Education and training of health cadres using lecture methods, procedure demonstrations, and examination simulations followed by question-and-answer discussions accompanied by pre-tests and post-tests to measure achievement targets. The measuring tool uses a questionnaire. 2. Cadre assistance is carried out by supervising procedures and mentoring health cadres in carrying out screening using stunting mats. The results of the activity showed that there was an increase in cadres' knowledge about stunting prevention in the post-test by 20 people (100%) with an average increase of 46 scores and an increase in cadres' skills in screening using the stunting mat method by 20 people (100%) with an average increase 81 scores. It can be concluded that this service activity has had an impact in increasing cadres' knowledge and skills regarding stunting prevention and screening. The cadres then apply their skills to the people in their area so that in the future the stunting rate in the Tapa sub-district can be reduced.